Management of Production Flow Using RTLS - Řezáč, Martin; Soušek, Radovan (International Institute of Informatics and Systemics, 2018)
The article focuses on practical use of Real Time Locating System (RTLS) in management of production flow. As the reference project, a project from the field of automotive was chosen as it is one of the most progressive and, at the same time, the most important industrial sectors of the present. The first part of the article describes the implementation and use of RTLS in the environment of final assembly of cars, and also directly usable outputs of this system. In the next part of the article, other ways of use of the system are outlined, based on data processing.
Řízení produkčního toku za použití RTLS
Keywords: RFID, RTLS, UWB, Industry 4.0, Automotive; RFID, RTLS, UWB, Průmysl 4.0, Automotive